Self-Reflection for English Teachers’ Pedagogical Development - Kuzairi; Welly Kuswanto; Agung Is Hardiyana Febry; Ali Wafa (EDUCAFL: Journal on Education of English as Foreign Language, 2024)
Reflection is a crucial part of teaching quality improvement. Teachers can learn a lot from what they did in the classroom dealing with their instructional activities. It indicates that qualified teachers are those who can evaluate and take meaningful reflection from their teaching experiences. This paper aims to expose the importance of self-reflection for English teachers’ pedagogical development as well as to describe how they carry out this one of the professional development activities to improve their instructions. A survey on investigating the professional development activities was conducted for 30 certified Senior High school English teachers as the technique in collecting the data. In addition, descriptive qualitative design was applied to present the findings of this study. The results show that among the 10 professional development activities that were proposed, Self-reflection was the highest choice with 73.17% of participants indicating that they commonly did it for their professional development. They had Self-Reflection by just asking the students to write comments or suggestions, requesting their students to answer some questions or give opinion on the teaching and learning process. Another simplest way was that teachers imagined on what they had done during the teaching and learning process and they made notes as references to develop their teaching performances. Another way of reflection is through recording the teaching and learning process. Regarding the results, it is recommended to regularly apply self-reflection as one of the essential professional development activities particularly in developing English teachers’ pedagogy